Pengaruh Campaigns terhadap Brand Jiniso.id yang di Endorsement untuk Kalangan Post-Millennials pada Sosial Media Instagram - Bella Novita; Rojuaniah Rojuaniah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
In today's digital era, social media has an important role in everyday life, one of which is as a communication channel. This research investigates the impact of brand familiarity, campaigns and brand experiences on brand attitude. This research is a quantitative approach and uses Structural Equation Modeling (SEM-PLS) analysis. The population in this study is the post-millennial generation who are active users of Instagram social media, have used or purchased Jiniso brand jeans fashion products, and live in the Jabodetabek area. This research uses a non-probability sampling method with a purposive sampling technique with a sample size of 182 respondents. Based on the research results, of the 7 hypotheses there are 5 hypotheses that are accepted, namely brand familiarity has a positive effect on campaign credibility, campaign fit has a positive effect on campaign credibility, campaign credibility has a positive effect on campaign attitude, campaign attitude has a positive effect on brand attitude, and brand experience has a positive effect on brand attitude. There are 2 hypotheses that were rejected, namely brand familiarity has no effect on brand attitude and involvement with the cause has no effect on campaign attitude. Based on these results, Jiniso is advised to improve and strengthen campaign strategies and marketing methods that can enable post-millennials to increasingly talk about their products on digital media.